2000
DOI: 10.1542/peds.105.4.738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Infection Control Measures on the Frequency of Upper Respiratory Infection in Child Care: A Randomized, Controlled Trial

Abstract: This trial supports the role of direct transmission of colds in young children in child care. The ability of infection control techniques to reduce episodes of colds in children in child care was limited to children 24 months of age and under.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
125
1
9

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(142 citation statements)
references
References 13 publications
7
125
1
9
Order By: Relevance
“…Given the contribution of direct transmission of pathogens to the prevalence of ARI in children in a day care, as well as the limited ability to reduce incidence of ARI through infection control techniques, 45 alternative measures such as nutritional supplementation should be considered. Cow' s milk is a regularly consumed beverage after 1 year of age.…”
Section: Discussionmentioning
confidence: 99%
“…Given the contribution of direct transmission of pathogens to the prevalence of ARI in children in a day care, as well as the limited ability to reduce incidence of ARI through infection control techniques, 45 alternative measures such as nutritional supplementation should be considered. Cow' s milk is a regularly consumed beverage after 1 year of age.…”
Section: Discussionmentioning
confidence: 99%
“…28 An Australian Capital Ter ritory repor t suggested that there were approximately 11 colds per child-year. 29 A study of South Australian preschool children reported a point prevalence of 32.6% and 33.7% for 'head colds' and 'dry cough' respectively. 30 Although cross-sectional studies cannot be directly compared with our findings, they corroborate the frequent occurrence of acute respiratory symptoms in the community.…”
Section: Discussionmentioning
confidence: 99%
“…890 In several other studies in which hand hygiene compliance was not monitored, multidisciplinary programmes that involved the introduction of an alcohol-based handrub were associated with a decrease in HCAI and cross-transmission rates. 429,489,645,735 The beneficial effects of hand hygiene promotion on the risk of cross-transmission have also been reported in surveys conducted in schools or day-care centres, 454,[891][892][893][894][895][896] as well as in community settings. 248,249,449,754,815,830,[897][898][899][900] While none of the studies conducted in the health-care setting represented randomized controlled trials, they provide substantial evidence that increased hand hygiene compliance is associated with reduced HCAI rates.…”
Section: Impact Of Improved Hand Hygienementioning
confidence: 95%